2022
DOI: 10.1037/xlm0000901
|View full text |Cite
|
Sign up to set email alerts
|

Stimulus-based mirror effects revisited.

Abstract: The mirror effect is the finding that in recognition tests, a manipulation that increases the hit rate also decreases the false alarm rate. For example, low frequency words have a higher hit rate and a lower false alarm rate than high frequency words. Because the mirror effect is held to be a regularity of memory, it has had a pronounced influence on theories of recognition. We took advantage of the recent increase in the number of linguistic databases to create sets of stimuli that differed on one dimension (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
22
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(25 citation statements)
references
References 48 publications
3
22
0
Order By: Relevance
“…For the latter, the Bayes factor indicated positive evidence for the null hypothesis, BF 01 = 6.99. The results are the same as those observed when using highly controlled stimuli in item recognition (Neath et al, in press) and differ from the mirror effect reported with concreteness in associative recognition (Hockley, 1994).…”
Section: Resultssupporting
confidence: 76%
See 4 more Smart Citations
“…For the latter, the Bayes factor indicated positive evidence for the null hypothesis, BF 01 = 6.99. The results are the same as those observed when using highly controlled stimuli in item recognition (Neath et al, in press) and differ from the mirror effect reported with concreteness in associative recognition (Hockley, 1994).…”
Section: Resultssupporting
confidence: 76%
“…Although subjects could potentially rely on the familiarity of the emergent associations between items, it is more likely that intact decisions are made when subjects specifically remember studying two items together (i.e., recollection). This difference in utility of familiarity and recollection for the two tests can account for the pattern of results observed here and by Neath et al (in press).…”
Section: Discussionsupporting
confidence: 56%
See 3 more Smart Citations